Oxyfuel combustion and reactants preheating to enhance turbulent flame stabilization of low calorific blast furnace gas. (15th April 2019) - Bâ, Abou; Cessou, Armelle; Marcano, Niomar; Panier, Faustine; Tsiava, Rémi; Cassarino, Guillaume; Ferrand, Ludovic; Honoré, David
Abstract: The need for the reduction of the environmental impact of combustion systems in terms of pollutant emissions and preservation of non-renewable resources forces to consider the improvement of energy efficiency and to turn towards alternative fuels in industrial combustion furnaces. However, their use may be an issue because of their low calorific value (LCV) compared to traditional natural gas (NG). The present work considers the combination of oxyfuel combustion with fuel and/or oxygen preheating in order to increase thermal efficiency by heat recovery and enhance LCV oxyfuel flame stabilization, without using a supporting fuel as NG. The study is focused on Blast Furnace Gas (BFG) which has one-tenth the heating value of NG. This assessment starts with thermochemical calculations of major flame properties at several reactant temperatures. Two fundamental flame configurations are simulated: a fully premixed 1D flame for the determination of adiabatic temperature, thermal thickness and laminar burning velocity, and a counter-flow diffusion flame for the determination of extinction strain rates. The results show that significant enhancement of oxyfuel flame properties can be obtained thanks to the preheating of BFG and oxygen. The effect of such preheating is then experimentally studied at laboratory-scale (25 kW) using a tri-coaxial burner generating a non-premixed turbulent BFG-O2 flame. The burner geometry consists of an annular BFG injection surrounded by an inner central oxygen injection and an external annular oxygen injection. Based on a critical Damköhler number, a theoretical analysis of the stabilization limit for a turbulent diffusion BFG-O2 flame with preheated reactant is described and used as a criterion to calculate the burner dimensions. Detailed flame characteristics are investigated from measurements of flue gas emissions and OH* chemiluminescence imaging. From these, the analysis of flame stability diagrams as function of reactant velocities, thermal power, oxygen distribution and preheating temperatures points out the limits of flame stability and the stable combustion regimes achieved at the different operational conditions. Regarding the emissions, very low levels of pollutant emissions such as CO and NOx are achieved in most cases. Further analysis of the results shows that transitions between the various types of flames are controlled by a critical convection velocity in the BFG – oxygen mixing layer. This is quantified from the measurements and matches with the theoretical prediction. Complementary large-scale experiments are performed on a semi-industrial facility, with identical burner geometry, scaled-up to 180 kW using the velocity criterion. The flames show similar structures as obtained at laboratory scale, demonstrating the benefit of preheated oxyfuel combustion for the stabilization of LCV flames. These results validate the analysis of the physical phenomena controlling the limit of stability of BFG oxyfuel flames, as well as the burner design strategy of preheated oxyfuel combustion adapted to low calorific fuels, and the scale-up criteria used for this particular case.